Correlates of achievement in analytic geometry of the first year Bachelor of Technology students at TUP Cavite SY 1996-1997 - Nunez, Susan L. (Animo Repository, 1997)
This study determines the different factors associated with achievement in Analytic Geometry of the first year Bachelor of Technology students at TUP Cavite campus during the second semester of school year 1996-1997. Specifically, it determines the degree of of relationship between achievement in Analytic Geometry and a) students-related factors as high school math grade, TUPSTAT-Math score, final grade in Math 111 (College Algebra), attitude towards mathematics and reading comprehension, b) teacher-related factors such as academic preparation and employment status. It also identified the variables that are significant predictors of achievement in Analytic Geometry.T he subjects of the study were 123 students who were enrolled in the seven technology areas of the BTech Program during the second semester of school year 1996-1997. They were selected through proportional stratified random sampling. Instruments like the Mathematical Attitude Inventory prepared by Dr. Milagros D. Ibe and the Reading Comprehension Test of the 1978 edition of the Metropolitan Achievement Test were used to gather data on attitude towards mathematics and reading comprehension, respectively. Other data were obtained from the academic records of students at the Registrar's Office of the University, and the Department of Mathematics and Science. The Human Resources Management (HRM) Office furnished the data on teacher's academic preparation and employment status. To complete the data, The TUPSTAT-Math scores were obtained from the Guidance Office. Mean, standard deviation, Pearson-Product Moment Correlation, Stepwise Multiple regression and the two-way analysis of variance were used in the statistical treatment of data. All statistical computations were done with the use of the SPSS computer package. The study found out the following:1. Among the independent variables, only the student-related ones were found to significantly correlate with achievement in Analytic Geometry.2. The amount of learning gained by the students in Analytic Geometry is not in any way affected by the academic preparation and employment status of their teachers.3. The final grade in Math 111 and TUPSTAT-Math score are the only valid predictors of achievement in Analytic Geometry. The best single predictor is final grade in Math 111.